EFFECTIVENESS OF dIMCI TRAINING IN DISTRICT ABBOTTABAD, KHYBER PAKHTUNKHWA: AN EXTERNAL PILOT STUDY - Saidul Abrar; Assad Hafeez; Muhammad Naseem Khan; Haroon, Muhammad Zeeshan; Ayesha Khan (Journal of Ayub Medical College Abbottabad, 2021)
Background: Five million deaths per year in under-five children are reported to be due to preventable and treatable causes. IMCI strategy targets these causes through improvement in the case management skills of health care workers. The objectives of this study were to identify eligible clusters and identify & rectify any process, resources, and management-related issues for the main trial. Methods: This study was conducted in two phases. Phase 1 was conducted for eligibility of Basic Health Units from which sample can be drawn for the main cluster randomized control trial. A single-page proforma was sent to all 54 BHUs of Abbottabad through registered mail service and replies received were analysed through SPSS-V25 and MS Excel-2016. Afterward a sample of 26 BHUs was drawn for the definitive trial. In phase 2, four BHUs were conveniently selected from the remaining sampling frame; one in the control arm while three in the intervention arm. From each BHU, a health care worker responsible for under-five consultations was trained; control arm in standard IMCI while intervention arm on distance learning IMCI. Ten observations in the form of cases managed were assessed at each BHU by a gold standard IMCI master trainer after a specific period. Descriptive summary measures and 95% CI were calculated using SPSS-V25. Results: Out of 54 BHUs, 3 were nonrespondents while 36 were identified as an eligible sampling frame. The mean index of integrated assessment was found to be 0.90 and 0.89 for the control and intervention arm respectively. Discrepancies in filled forms were noted as 60% in control while 63.3% in intervention arm. Conclusion: Modifications in the plan for the main trial based on the findings of pilot study can ensure credibility and rigor in the definitive trial.